2018
DOI: 10.3390/ijms19010119
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and the Relationship with Bone Fragility Fractures in HIV-Infected Patients: A Case Control Study

Abstract: HIV-infected patients show high risk of fracture. The aims of our study were to determine the prevalence of vertebral fractures (VFs) and their associations with vitamin D in HIV patients. 100 patients with HIV infection and 100 healthy age- and sex-matched controls were studied. Bone mineral density was measured by quantitative ultrasound at the non-dominant heel. Serum osteocalcin and C-terminal telopeptide of collagen type 1 served as bone turnover markers. Bone ultrasound measurements were significantly lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…The role of nutrition in maintaining bone health associated with a personalized anti-HIV treatment and daily vitamin supplementation to reduce early bone loss as well as a baseline DXA are critical steps for HIV Migrants and Refugees after arrival in the host countries [13,17,20,23,36]. High-risk groups should be first identified, and osteoporosis investigations should be carried out earlier than at 50 years of age [37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…The role of nutrition in maintaining bone health associated with a personalized anti-HIV treatment and daily vitamin supplementation to reduce early bone loss as well as a baseline DXA are critical steps for HIV Migrants and Refugees after arrival in the host countries [13,17,20,23,36]. High-risk groups should be first identified, and osteoporosis investigations should be carried out earlier than at 50 years of age [37][38][39].…”
Section: Plos Onementioning
confidence: 99%
“…Vitamin D deficiency is inseparably connected to demineralization of bones, which results in an increased susceptibility to fractures. Atteritano and coworkers presented a case study showing the relation between low vitamin D levels and susceptibility to bone fragility fractures in HIV-positive patients [5]. De Luca et al showed that the presence of specific alleles of FokI single nucleotide polymorphism (SNP) in the vitamin D receptor (VDR) gene affects cell proliferation and inflammatory response.…”
Section: Vitamin D and Healthmentioning
confidence: 99%
“…(28) There are no studies on mortality and quality of life in HIV þ individuals after a fracture. Nonetheless, just as in (6,32,38) Chronic inflammation (55) Previous fractures (38,59) Reconstitution syndrome (55) Low BMI (32,37,60,61) ART use (8,15,20,27) Tobacco use (38,62) Co-infection with hepatitis B (79) Alcohol abuse (63) Co-infection with hepatitis C (33,80,81) Glucocorticoid use (63) Low CD4 (31,32,38,81) Anticonvulsant use (59) AIDS-defining disease (81) Postmenopausal status (6,24,26) Hypogonadism (38,64) Vitamin D deficiency (24,(65)(66)(67) White race (8,27) Diabetes mellitus (59) Frailty (69) Sarcopenia (38) Selective serotonin reuptake inhibitors (70) Comorbidities (72) Falls (59) R...…”
Section: Morbidity and Mortality Of Bone Disease In Hiv Subjectsmentioning
confidence: 99%